Prevalence and correlates of mental health problems among different occupations of medical workers during COVID-19 outbreak in China - Yan, Qiuping; Hou, Xiaofei; Zhang, Tingting; Yin, Huifang; Han, Bing; Ma, Chao; Wang, Ying; Chen, Hongguang; Wen, Jing; Huang, Yueqin; Jiang, Rongmeng; Liu, Zhaorui; et al. (Frontiers in Public Health, 2024)
Background Health workers involved in the fight to prevent the COVID-19 outbreak were exposed to hazards. Detailed information on mental health problems in different medical occupations is crucial. To examined the prevalence of mental health issues in three medical occupations as well as the relationships between mental health problems and correlates in each occupation. Methods This study utilizing the Questionnaire Star program was conducted among medical workers working at medical institutions in China from February 17 to 24, 2020. The Self-Reporting Questionnaire (SRQ-20), the Zung Self-rating Anxiety Scale (SAS), and the Zung Self-rating Depression Scale (SDS) were used to assess mental health problems. Results The prevalence of any mental health problems in the three occupations was 43.6, 34.6, and 32.9% for nurses, paramedical workers (PMWs), and doctors, respectively. Three occupations shared some correlates, such as being overworked, not having enough time to rest, support from colleagues, and previous mental health status. There were specific factors for each occupation. For doctors, age, educational level, living status, support from family, and previous physical status were related factors in mental health problems. Working in a designated hospital for treating COVID-19, having COVID-19 event exposures, and receiving support from family were associated with the mental health problems of the nurses. PMWs’ mental health problems was linked to educational level and care from supervisors or heads of department. Conclusion Different medical occupations have distinct impacts on mental health issues. Policy makers and mental health professionals working to prepare for potential disease outbreaks should be aware of multiple factors in different occupations.